Wildland fire behaviour dynamics, principles and processes - Finney, Mark Arnold; McAllister, Sara; Grumstrup, Torben P.; Forthofer, Jason M. (CSIRO Publishing, 2021)
Wildland fires have an irreplaceable role in sustaining many of our forests, shrublands and grasslands. They can be used as controlled burns or occur as free-burning wildfires, and can sometimes be dangerous and destructive to fauna, human communities and natural resources. Through scientific understanding of their behaviour, we can develop the tools to reliably use and manage fires across landscapes in ways that are compatible with the constraints of modern society while benefiting the ecosystems. The science of wildland fire is incomplete, however. Even the simplest fire behaviours - how fast they spread, how long they burn and how large they get - arise from a dynamical system of physical processes interacting in unexplored ways with heterogeneous biological, ecological and meteorological factors across many scales of time and space. The physics of heat transfer, combustion and ignition, for example, operate in all fires at millimetre and millisecond scales but wildfires can become conflagrations that burn for months and exceed millions of hectares."Wildland Fire Behaviour: Dynamics, Principles and Processes" examines what is known and unknown about wildfire behaviours. The authors introduce fire as a dynamical system along with traditional steady-state concepts. They then break down the system into its primary physical components, describe how they depend upon environmental factors, and explore system dynamics by constructing and exercising a nonlinear model. The limits of modelling and knowledge are discussed throughout but emphasised by review of large fire behaviours. Advancing knowledge of fire behaviours will require a multidisciplinary approach and rely on quality measurements from experimental research, as covered in the final chapters